THE FORMULATION AND PHYSICAL PROPERTY TEST OF LIP TINT PREPARATION FROM MANGOSTEEN PEEL EXTRACT (Garcinia mangostana L.) AS A NATURAL COLOR - Haniva Haika; Ayu Angger Putri (LPPM Universitas dr. Soebandi, 2025)
The development of technology in this modern era has increased the demand for beauty products, especially lip colorants such as lip tint, continues to increase. However, many commercial products contain harmful ingredients that can cause irritation. As an alternative, natural colorants are safer. Mangosteen rind (Garcinia mangostana L.) can be used as a natural colorant and contains xanthones, anthocyanins, saponins, and tannins. To determine whether varying concentrations from mangosteen peel extract (Garcinia mangostana L.) affect the physical properties and hedonic evaluation of lip tint preparations. This study used a laboratory experimental design. The sample used was mangosteen fruit peel extract (Garcinia mangostana L.) obtained by Ultrasonic Assisted Extraction (UAE) method using 96% ethanol solvent with a ratio of (1:5). Evaluation of the preparation includedEvaluation of physical characteristics (appearance, uniformity, pH level, ability to spread and stickiness) and hedonic test. Data were analyzed using SPSS 25.